Graduate skills requirements for effective performance in the banking sector - Cicekli, Elif (Business: Theory and Practice, 2016)
This paper aimed to explore the graduate skills requirements in the banking sector. In-depth interviews were carried out with twenty-five managers in ten companies in the banking industry in Turkey. The results show that 40 percent of managers thought universities do not provide their graduates with the skills necessary to be successful in their jobs. Soft skills (i.e. communication, interpersonal relationship, and teamwork skills) are particularly sought after, and managers would also like to see more training in analytical thinking skills. Researchers are recommended to study the subject in different counties using quantitative methods. Based on results, bank executives are advised to communicate and collaborate with educators to make sure their needs are known and met. This paper filled the gap in research on the skills the banking sector needs in new graduates.